Long Non-coding RNA ANRIL in the Nucleus Associates With Periostin Expression in Breast Cancer - Mehta-Mujoo, Paulomi M.; Cunliffe, Heather E.; Hung, Noelyn A.; Slatter, Tania L. (Frontiers in Oncology, 2019)
The long non-coding RNA (LncRNA) antisense RNA in the INK4 locus (ANRIL) is overexpressed in several cancers including breast cancer. To better understand the role of ANRIL in breast cancer this study investigated where ANRIL was expressed in breast tumors using in situ hybridization by RNAscope. Additional RNAscope assays for IL6, CCL2, and POSTN were used to establish whether ANRIL correlated with increased tumor promoting cytokines. Breast tumors with ANRIL over expressed from real-time quantitative (RT-q) PCR assays were selected for analysis using RNAscope. All tumors showed ANRIL expression in malignant cells, but amongst tumors ANRIL showed different subcellular locations with 56% of tumors with ANRIL only in the nucleus, 16% with ANRIL only in the cytoplasm and 28% with ANRIL in both the nucleus and cytoplasm. Cases with nuclear ANRIL were positively correlated with POSTN expression in malignant cells (rho = 0.57, P = 0.0086), and no correlation was found between ANRIL and IL6 or CCL2. Reduced POSTN was also found using siRNA to ANRIL in MDA-MB-231 and MCF7 breast cancer cells. These data indicate that ANRIL is expressed in malignant breast cells, and suggest its subcellular location may indicate its function in cancer progression.